Insights from an Intervention to Support Early Career Faculty with Extraprofessional Caregiving Responsibilities - Lauren A. Szczygiel; Rochelle D. Jones; Amelia F. Drake; Wonder P. Drake; Daniel E. Ford; Katherine E. Hartmann; Anne M. Libby; Bess A. Marshall; Judith G. Regensteiner; Kristine Yaffe; Reshma Jagsi (Mary Ann Liebert, 2021)
Background: Insufficient support for balancing career and family responsibilities hinders retention of physician-scientists. Programs to improve retention of this important group of faculty are crucial. Understanding the experiences of program implementers is key to refining and improving program offerings. Methods: We conducted an interpretive, descriptive, and qualitative study as part of an ongoing evaluation of the Doris Duke Charitable Foundation's Fund to Retain Clinical Scientists (FRCS) awards. We conducted telephone interviews with 12 program directors representing all 10 US medical schools who received the Doris Duke funding in 2016. Results: Of the 12 participants, 10 were women (83.3%). Participating program directors perceived the FRCS award as capable of producing paradigmatic changes regarding how responsibilities at home and work in academic medicine are viewed and integrated by early-career faculty members. The main qualitative themes that captured directors' experiences implementing the program were as follows: (1) championing a new paradigm of support, (2) lessons learned while implementing the new paradigm, (3) results of the new paradigm, and (4) sustaining the paradigm. Conclusions: These findings may help to inform development of similar programs to retain and support the career progress of physician-scientists with extraprofessional caregiving responsibilities. The interviews illuminate ways in which the Doris Duke FRCS award has driven institutional culture change by normalizing discussion and prompted reassessment of extraprofessional challenges and how best to aid early-career faculty members in overcoming these challenges.